2021
DOI: 10.2147/jbm.s213510
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Drug Interference in Transfusion Testing: A Spotlight on Daratumumab

Abstract: Daratumumab, a monoclonal antibody therapeutic, is highly efficacious and widely used in all stages of multiple myeloma and amyloidosis and has promising activity in other hematologic disorders. Daratumumab interacts with red blood cells, interfering with pre-transfusion testing. This interference can lead to compromising transfusion safety, extensive blood bank work ups and delays in provision of compatible units. Several methods have been developed to negate daratumumab interference with indirect antiglobuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…To avoid significant delays in patient care, it is recommended to determine blood typing prior to first infusion [ 35 ]. If unobtainable, dithiothreitol (DTT) may be used to determine blood type post-daratumumab infusion [ 36 ].…”
Section: Pharmacologic Agentsmentioning
confidence: 99%
“…To avoid significant delays in patient care, it is recommended to determine blood typing prior to first infusion [ 35 ]. If unobtainable, dithiothreitol (DTT) may be used to determine blood type post-daratumumab infusion [ 36 ].…”
Section: Pharmacologic Agentsmentioning
confidence: 99%
“…Plasma samples from patients receiving anti‐CD38 consistently cause positive agglutination reactions in antibody detection tests (screens), antibody identification panels, and antihuman globulin cross matches, complicating pretransfusion testing and potentially delaying patient blood support. Several strategies have been employed to negate the anti‐CD38 interference, each with advantages and disadvantages 6 . The most common method is to treat reagent cells with 0.2 M dithiothreitol (DTT).…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been employed to negate the anti-CD38 interference, each with advantages and disadvantages. 6 The most common method is to treat reagent cells with 0.2 M dithiothreitol (DTT). DTT denatures cell surface CD38, eliminating the anti-CD38 interference.…”
Section: Introductionmentioning
confidence: 99%
“…During the study of above projects, routine blood screening in blood banks showed consistently positive Indirect Anti-human globulin Test (IAT) results among patients who received daratumab therapy [9,10] . IAT, also called indirect Coombs test, typically used to test Red Blood Cell (RBC) alloantibody compatibility in plasma prior to transfusion [11,12] . Since CD38 is expressed on human erythrocytes, daratumumab may interfere with IAT by binding to endogenous CD38 present on the surface of RBC [12,13] .…”
mentioning
confidence: 99%
“…IAT, also called indirect Coombs test, typically used to test Red Blood Cell (RBC) alloantibody compatibility in plasma prior to transfusion [11,12] . Since CD38 is expressed on human erythrocytes, daratumumab may interfere with IAT by binding to endogenous CD38 present on the surface of RBC [12,13] . In relapsed and refractory MM treatment, patients often have anemia and frequent need for blood transfusions, therefore, find and establish a blood group antibody screening and cross-matching program that excludes anti-CD38 monoclonal antibody interference has become an urgent problem to be solved in the blood transfusion department.…”
mentioning
confidence: 99%